A PD-edge method associated with the laser autocollimation for measurement of a focused laser beam diameter. (24th May 2018) - Shimizu, Yuki; Maruyama, Taiji; Nakagawa, Shota; Chen, Yuan-Liu; Matsukuma, Hiraku; Gao, Wei
Abstract: For measurement of a focused laser beam diameter, a new method, referred to as the PD-edge method, in which an edge of an active cell in a photodiode (PD) is directly employed in the same manner as a knife-edge or a knife-pad in the conventional methods, is proposed with the enhancement of the principle of laser autocollimation. In the proposed PD-edge method associated with the laser autocollimation, a focused laser beam diameter can be estimated by using the gradient of output signal from the PD with respect to the change in the angle of incidence of a collimated laser beam made incident to an objective lens. In this paper, the feasibility of the proposed PD-edge method is at first verified in computer simulation. After that, the edge sensitivity characteristic of an active cell in a commercially available PD is investigated in experiments as well as in computer simulation based on the simple edge-transmission region model to search for the possibility of directly employing a commercially available PD for measurement of a focused laser beam diameter. Furthermore, an optical setup is constructed, and some experiments as well as the measurement uncertainty analysis are carried out to verify the feasibility of the proposed PD-edge method.